Viabilitas Benih Jagung Lokal yang diberi Tepung Daun Tembelekan (Lantana camara Linn) dalam Pencegahan Serangan Sitophilus zeamais Motsch (Coleoptera:Curculionidae) Selama Penyimpanan - Anna Tefa; Alexander Kehi Klau; Origenes Boy Kapitan (Fakultas Pertanian, Universitas Timor, 2019)
Sitophilus zeamais Motsch (Coleoptera: Curculionidae) commonly attack the maize grains during the storage period so as to reduce the seed viability. The tembelekan plant (Lantana camara linn) produce various secondary metabolites which can be used to protect maize grains from the maize weevil attack.. Investigation was carried out to determine the effect of the tembelekan leaf flour (L. camara Linn) in controlling the maize weevil and to study the effect of tembelekan leaves in maintaining viability of maize grains during storage. This study uses a completely randomized design with factorial design. The first factor is the tembelekan flour dosege which consist of four levels i.e T0: without flour, T1: 10% w/w, T2: 15% w/w, T3: 20% w/w. The second factor is exposure time which consist of three levels i.e M0: 1 week, M1: 2 weeks, dan M2: 3 weeks. The results showed that the interaction of the treatment of tembelakan leaf flour and storage period was able to maintain the maize seed viability and vigor parameters i.e maximum germination potential in the amount of 97.33%, seedling growth rate in the amount of 19.06%etmal, seedling vigor index in the amount of 71% and seedling dry weight in the amount of 5.4 grams.